Optimizing Learning Environments: Harnessing the Power of Effective Education Management Practices for High School Student Success in West Java - Haetami (Westscience Press, 2023)
This research delves into the correlation between effective education management practices and high school student success in West Java, Indonesia. Employing a mixed-methods approach, the study investigates how optimized learning environments contribute to improved academic outcomes. Quantitative data is collected through surveys from teachers, administrators, and students, while qualitative insights are gathered through interviews with education experts. The findings reveal positive correlations between teacher training, student engagement, and academic achievement. Recommendations are provided for curriculum design, teacher development, and collaborative practices to enhance the quality of education in the region.